The Law Applicable to Damages Resulting from Discriminatory Algorithms - Khalifa, Attia Suleiman (International Journal of Law and Public Policy (IJLAPP), 2026)
The growing use of algorithmic and artificial intelligence systems in decision-making process have produced new forms of discrimination that cross borders and which traditional legal means are insufficient to address. This study aims to explore the problem that complicated in case of harm caused by discriminatory algorithms especially from the private international law angle: which law should apply to damages arising therefrom? Applying a doctrinal and comparative legal approach, the study investigates European Union (EU) private international law, certain national legal orders and international soft law instruments in the field of algorithmic discrimination and Artificial Intelligence. The research shows that old connecting factors such as lex loci damni tend to become less applicable in algorithmic harm cases, because they were not written for a globally diffused phenomenon with no humanly perceptible terrestrial extension as is the case of the online sphere. Recent regulatory initiatives (especially in data protection and AI governance) are reinforcing the substantive guarantees against discrimination, but do not respond explicitly to applicable law queries: They concentrate on appropriate measures that should accompany technical AI development. The article suggests that existing conflict-of-laws regimes should be updated to foster more effective victim protection and legal predictability. It proposes the use of victim-oriented connecting factors, the application of fundamental rights as an ius cogens, and explicit conflict-of-law clauses in specific AI regulation. These changes are necessary for closing the accountability gap and providing for meaningful redress of harm from discriminatory algorithms in cross-border situations.